ANALISIS FAKTOR YANG MEMPENGARUHI HASIL BELAJAR IPA DAN LITERASI SAINS DI SMP NEGERI 1 MUARO JAMBI - Jufrida, Jufrida; Basuki, Fibrika Rahmat; Pangestu, Miko Danu; Djati Prasetya, Nugroho Asmara (EduFisika: Jurnal Pendidikan Fisika, 2019)
The research aims to analyze the factors that affect science learning outcomes and scientific literacy. This study used a qualitative descriptive approach with the case study type. The subject of this research was 1 teacher and grade IX students SMPN 1 Muaro Jambi as much as 37. The research instruments use questioner and documentation. Data were analyzed in a qualitative descriptive. The factors that affect the learning outcome and scientific literacy were psychological factors (interest and learning motivation), family factors (background of education and guidance of parents), school factors (teaching methods, teachers, facilities and institutions, and teaching materials/media), and learning activities outside school.